Finding Humanity in Design - Quinn, Erin; Bartlett, Stephanie; Alisat, Laurie; McNeil, Sandra; Miner, Kim (Journal of the Canadian Association for Curriculum Studies, 2018)
The Calgary Board of Education’s Design the Shift was a radical step away from typical professional development opportunities. It was a year-long collaboration designed for educators to provoke a shift in practice by redefining curriculum through design. Our definition of design evolved from a linear business model to a much more generous movement. As designers of learning, the participants took up “what really [mattered] to them”, with design becoming an intersection of creativity, place, and community (Chambers, 1998, p. 17). We created opportunities for participants to charge up against an experience, causing them to make, unmake, and remake the curriculum of their classrooms. All experiences inspired the participants to stop, notice, listen and awaken, drawing on Maxine Greene’s (1977) wide-awakeness philosophy.